Islamic bonds and the wealth effects: Evidence from Malaysia - Ibrahim, Yusnidah; Minai, Mohd Sobri (LLC “СPС “Business Perspectives”, 2009)
The fast growing numbers of Islamic bonds issuance in Malaysia and worldwide, coupled with the lack of corporate finance literature that integrates the development of Islamic capital market motivate the study on the wealth effects of Islamic debt offerings and their determinants.It is found that the market reaction is significantly positive during event windows -3, 0 and -3, 3 surrounding the announcements of Islamic debt issuance.Five variables suggested by the capital structure literature, namely firms size (SIZE), issue size (AMT), leverage (LEV), free cash flows (FCF) and investment opportunity (TQ) together with two new variables, the syariah compliant status (SYAR) and the Security Commission’s (SC) approval (APPROVAL) were modeled as potential explanatory variables of the wealth effects.The study concludes that the wealth effect of Islamic bond issuance announcements is positively influenced by the issuer’s investment opportunity and negatively influenced by the issue size, firm size and whether the announcement is accompanied by the SC approval.The finding implies that the positive reaction is not due to investors’ preference for Islamic compliant activities but it is due to similar factors found in studies on conventional bonds.The negative influence of SC approval on the wealth effect indicates that many listed companies issuing Islamic debt are not complying with the information disclosure requirement.